KARAKTER TRIKOMA DAUN TANAMAN JATI (Tectona grandis L.) YANG DITANAM PADA TANAH PASCATAMBANG EMAS BOMBANA DENGAN VARIASI DOSIS PUPUK KANDANG KAMBING - Ambardini, Sri; Indrawati, Indrawati; Ratnaen, Ratnaeni (Jurnal BioWallacea, 2015)
The purpose of this study was to determine: the character trichomes of the plant teak(Tectona grandis L.) planted on gold post-mining soil Bombana with variation dose of goatmanure. This research is experimental use completely randomized design with 4 treatment,namely without goat manure (control/K0), and treatment of goat manure 100g 10kg-1 soil(K1), 125g 10kg-1 soil (K2), and 150g 10kg-1 soil (K3) in repeated 3 times. Teak plantparameters observed were the levels of length and number trichomes on the side abaksialand adaksial leaves (Tectona grandis L.). The results showed that goat manure of thetreatments K2 gives the highest value of length trichomes abaksial (995,46 Î¼m), highestlength trikomes adaksial K0 (406,203Î¼m). The biggest number trikomes abaksial on K3(3,481) and biggest number trichomes adaksial on K3 (4,047) too. Three character anatomyof trichomes was found in this research, namely dichotome multiselluler type on the abaksialleaf surface, slim uniselluler and biselluler type on the adaksial leaf surface.Key words: Teak (Tectona grandis L.), Goat manure, post-mining soil, trichomes.